Action of rain on formulations of glyphosate mixed with saflufenacil for the control of Brachiaria decumbens - Costa, Andréia Cristina Rodrigues Da; Gonçalves, Clebson Gomes; Silva Junior, Antonio Carlos Da; Cardoso, Leonildo; Martins, Dagoberto (Instituto Biológico, 2017)
ABSTRACT: This study aimed to evaluate the effects of rain on the efficiency of different formulations of glyphosate applied in isolation and in combination with saflufenacil on the control of Brachiaria decumbens. This study was conducted during the first half of 2013. The treatments consisted of an isolated application of three formulations of glyphosate (Roundup Original, Roundup Transorb R, and Roundup WG) at 1,080 g a.e. ha-1 and mixed with saflufenacil at 24.5 g a.e. ha-1 + Dash at 0.5% v/v at six time intervals of simulated rain: 15, 30, 60, 120, 240 and 360 minutes after application of herbicides and a control treatment without rain. We performed visual evaluations of plant control at 4, 7, 14, 21 and 28 days after application of herbicides. The mixture of saflufenacil + Dash with the original Roundup formulations, Roundup Transorb R and Roundup WG increased the control speed of B. decumbens plants regardless of the rain interval studied. The formulations of glyphosate (Roundup Transorb R and Roundup WG) applied in isolation were affected by rains that occurred shortly after spraying. In combination with saflufenacil + Dash, there was a synergistic effect on weed control.

RESUMO: O objetivo do trabalho foi avaliar a ocorrência de chuvas na eficiência de diferentes formulações de glyphosate aplicadas de forma isolada e em mistura com o saflufenacil, sobre o controle de Brachiaria decumbens. O estudo foi realizado no primeiro semestre de 2013. Os tratamentos constaram da aplicação isolada de três formulações de glyphosate (Roundup Original, Roundup Transorb R e Roundup WG) a 1.080 g e.a. ha-1 e em mistura com o saflufenacil a 24,5 g i.a. ha-1 + Dash a 0,5% v/v e, seis intervalos de tempo para simulação da chuva: 15; 30; 60; 120; 240 e 360 minutos após a aplicação dos herbicidas e uma testemunha sem chuva. Foram realizadas avaliações visuais de controle das plantas aos 4; 7; 14; 21 e 28 dias após a aplicação dos herbicidas. A mistura de saflufenacil + Dash às formulações de Roundup original, Roundup transorb R e Roundup WG aumentaram a velocidade de controle das plantas de B. decumbens, independente do intervalo de chuva estudado. As formulações de glyphosate (Roundup Transorb R e Roundup WG) aplicados isolados foram afetadas por chuvas que ocorreram logo após a pulverização e quando em mistura com saflufenacil + Dash observou-se efeito sinérgico no controle das plantas daninhas.
Ação da chuva em formulações de glyphosate em mistura com saflufenacil no controle de Brachiaria decumbens
Keywords: Brachiaria; efficacy; herbicide; weed; Brachiaria; eficácia; herbicida; plantas daninhas